KAJIAN FEMINIS PADA NOVEL "RONGGENG DUKUH PARUK" DAN "PEREMPUAN BERKALUNG SURBAN" - Indrya Mulyaningsih (Indonesian Language Education and Literature, 2015)
Literary work is a socio-cultural documentation. This is because the socio-cultural influence the creation of works of literature itself. Following the feminist studies on novel Ronggeng Dukuh Paruk and Perempuan Berkalung Surban. The research is a qualitative descriptive analysis technique document. Based on the analysis it can be concluded that the RDP and PBS equally raised about women, especially girls. Ronggeng Dukuh Paruk exploit girls economically while Perempuan Berkalung Surban not provide an opportunity for girls to determine their own lives. Both novels are equally illustrate inequities in girls.